Parámetros de calidad de las revistas científicas españolas sobre historia moderna y contemporánea - Mikelarena Peña, Fernando (Huarte de San Juan. Geografía e Historia, 2007)
In this article it is thought over on the measurement of the quality in the research on modern and contemporary history. There is compared the content of the last regulation of the CNEAI with the results of the Latindex project and with the results of several reports on the quality level of the spanish scientifist journals.